A novel fluorescent marking clip for laparoscopic surgery of colorectal cancer: A case report. (2019) - Narihiro, Satoshi; Yoshida, Masashi; Ohdaira, Hironori; Sato, Takayuki; Suto, Daisuke; Hoshimoto, Sojun; Suzuki, Norihiko; Marukuchi, Rui; Kamada, Teppei; Takeuchi, Hideyuki; Suzuki, Yutaka
Highlights: This is the first report on fluorescent marking clip for laparoscopic surgery. In laparoscopic surgery, marking of tumor location has been gaining importance. Tattoo marking technique carries the risk of accidental intestinal wall perforation leading to peritoneal scattering or other organ perforation. The fluorescent marking clips were easily placed and recognized with a fluorescent laparoscope. The fluorescent clip is expected to reduce risks related to other marking methods. Abstract: Introduction: In laparoscopic surgery, marking of tumor location has been gaining importance. Tattoo marking has been often used but the technique carries the risk of accidental peritoneal scattering or other organ injury. We have been involved in the development of a novel fluorescent clip for marking tumor sites and supposed that its usage would reduce risks related to other marking methods. Case presentation: A 52-year-old man was diagnosed with sigmoid colon cancer and polyp, and was scheduled for laparoscopic sigmoidectomy. On the day before operation, fluorescent clips (ZEOCLIP FS: Zeon Medical co, Ltd, Tokyo) were endoscopically placed around the tumor and polyp sites, 4 clips for each lesion attached every 90 degrees within the colonic lumen, respectively. During the operation, locations of the fluorescent clips were easily confirmed using a full-color fluorescent laparoscope, VISION SENSE (Medtronic Co., U.S.). Curative operation was performed accordingly with the preoperative pathological and radiological findings. The postoperative course was uneventful. Discussion: Locations of intraluminally placed fluorescent clips were clearly and easily recognized through the serosal layer of the intestinal wall using a fluorescent laparoscope. Complications related to dye scattering or intestinal wall/other organ perforation were not observed suggesting that future incorporation of this tumor site marking technique into laparoscopic surgery might be beneficial. Conclusion: The fluorescent marking clips were easily placed and recognized with a fluorescent laparoscope. This method is expected to be safe and risks of accidental puncture related to tattoo marking method can be reduced or almost eliminated.